Pemberdayaan Masyarakat Desa Berbasis Program Padat Karya Tunai Di Desa Tongkonan Basse Kecamatan Masalle Kabupaten Enrekang - Karmila, Karmila; Said, Alimuddin; Fatmawati, Fatmawati (Universitas Muhammadiyah Makassar, 2021)
This study aimed to determine the implementation process of Village Community Empowerment based on Cash-Intensive Work Program in Tongkonan Basse Village, Masalle District, Enrekang Regency. This type of research was qualitative research. Informants were 5 people. Data collection techniques were observation, interviews and documentation. The results of this study showed that in the process of implementing empowerment-based cash-intensive programs in the village of Tongkonan Basse, the Masalle district had been carried out since 2018, as for the forms of development of cash-intensive labor such as casting farm roads, making rainfalls, building road talud, building pustu (puskesmas helper) and latrine construction. And also be the community prefered gardening to participating in the cash-intensive development process. also in terms of empowerment, only a part of the community was empowered with the existence of this cash-intensive program, but when viewed in terms of village infrastructure development the community was prosperous and greatly helped in their daily activities.